Effect of Textured Tools on Machining of Ti-6Al-4V Alloy under Lubricant Condition. (2018) - Arulkirubakaran, D.; Senthilkumar, V.; Dinesh, S.; Velmurugan, C.; Manikandan, N.; Raju, Ramesh
Abstract: In this work, an attempt is made to reduce the detrimental effects that occurred during machining of Ti-6Al-4V by employing the textures on the rake faces of the cutting tools. Turning experiments on the Ti–6Al–4V alloy were carried out using textured tungsten carbide tools with micro-scaled grooves in preferred orientation such as, parallel, perpendicular and cross pattern to that of chip flow. A mixture of molybdenum disulfide with SAE 40 oil (80:20) was used as semi-solid lubricant during machining process. The feed, thrust and cutting forces were measured by a three component Kistler-dynamometer. The power consumption during machining was measured using Fluke 43B type power meter. Experimental results such as machining forces and power consumption were analyzed and compared. From the observation, cutting tools with textures produced in a direction perpendicular to that of chip flow exhibits a better in all the results aspects.